Method for evaluating thickness expansion rate of electrode sheet of lithium ion battery at half charge and full charge

CN116481477BActive Publication Date: 2026-10-09ZHENGZHOU BAK ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310398555.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-14
Publication Date
2026-10-09
Estimated Expiration
2043-04-14

AI Technical Summary

Technical Problem

由于受到石墨负极的影响,负极石墨在嵌锂的过程中会生成LiCx等化合物,造成分子之间晶格变化,形成微观的内应力,导致负极石墨端部分鼓胀;而粘结剂SBR和电解液对极片厚度的变化也会产生影响,充电时锂离子由正极嵌入负极,负极石墨晶格发生膨胀,负极颗粒与粘结剂SBR发生形变,负极处内应力得被释放,导致电池负极膨胀率增大

Benefits of technology

[0020]This invention can quickly calculate the electrode expansion rate at each stage by recording the electrode thickness of the lithium-ion battery at each stage. By disassembling the pre-charged half-charged and fully charged cells after capacity testing and recording the electrode thickness, the electrode thickness expansion rate of the lithium-ion battery under half-charge and full-charge conditions can be obtained. This invention is simple to operate, has high accuracy, and can effectively evaluate the electrode thickness expansion changes of lithium-ion batteries, which is beneficial for designing the initial thickness dimensions of pouch cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116481477B_ABST
    Figure CN116481477B_ABST
Patent Text Reader

Abstract

The application discloses a kind of lithium ion battery half electricity and full electricity under pole piece thickness expansion rate test method, the pole piece thickness of each stage of lithium ion battery is recorded in the application, the pole piece expansion rate of each stage can be quickly calculated, the pole piece thickness of half electricity after pre-charging and full electricity after equalization is recorded, the pole piece thickness expansion rate of lithium ion battery under half electricity and full electricity is obtained, the application is simple to operate, higher accuracy, can effectively test the pole piece thickness expansion rate of lithium ion battery, it is beneficial to evaluate the initial thickness size of design soft package battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of lithium battery testing methods, and in particular to a method for testing the electrode thickness expansion rate of a lithium-ion battery under half-charge and full-charge conditions. Background Technology

[0002] During the use of lithium-ion batteries, the thickness of the positive and negative electrodes changes, with the change being more pronounced in the negative electrode. After long-term storage and cycling, lithium batteries are prone to bulging. Due to the influence of the graphite negative electrode, compounds such as LiCx are generated during lithium intercalation, causing lattice changes between molecules and creating microscopic internal stress, leading to bulging at the graphite end of the negative electrode. The binder SBR and electrolyte also affect the change in electrode thickness. During charging, lithium ions intercalate from the positive electrode to the negative electrode, causing the graphite lattice to expand and the negative electrode particles and binder SBR to deform. This releases the internal stress at the negative electrode, resulting in an increased negative electrode expansion rate.

[0003] The thickness variations of the positive and negative electrodes in lithium-ion batteries directly affect the initial thickness design of the cell. Currently, there is a lack of effective methods to test the thickness variation rate of lithium-ion battery positive and negative electrodes under different states. This invention, for pouch polymer cells, studies the thickness variations of the positive and negative electrodes at different process stages to calculate the total thickness variation rate of the positive and negative electrodes in half-charge and fully charged states, facilitating the design of the initial cell thickness based on these electrode thickness variations. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for testing the electrode thickness expansion rate of lithium-ion batteries under half-charge and full-charge conditions.

[0005] The objective of this invention is achieved through the following technical solution: a method for testing the electrode thickness expansion rate of a lithium-ion battery under half-charge and full-charge conditions, comprising the following steps:

[0006] (1) Select the model, take the unrolled double-sided electrode sheet, punch it with a punching machine, weigh the electrode sheet weight and area, punch the empty foil, weigh the foil material weight and thickness, and calculate the areal density = (electrode sheet weight - foil material weight) / electrode sheet area.

[0007] (2) Based on the areal density and compaction parameters of the electrode sheet, roll the electrode sheet to thickness = areal density / compaction + foil thickness, and record it as the initial thickness T1;

[0008] (3) Place the electrode in the workshop and record the electrode thickness T2 after one day. When waiting for the conventional electrode to be wound, measure the thickness of the punched electrode T3. After the conventional electrode is sealed on the top and side, measure the thickness of the punched electrode T4 before baking.

[0009] (4) Place the electrode in an oven for vacuum baking and record the electrode thickness T5 after baking;

[0010] (5) Place the baked electrode into a material box containing electrolyte. After 36-48 hours, wipe the electrolyte off the surface of the electrode or wait for the electrolyte to evaporate completely. Record the electrode thickness T6.

[0011] (6) Control the rolling thickness of the experimental electrode to the middle limit of the design thickness and record the electrode thickness T0;

[0012] (7) Disassemble the lithium battery cells at 50% SOC half charge after pre-charging and 100% SOC full charge after capacity grading, and record the electrode thickness T7 after pre-charging and the electrode thickness T8 after capacity grading.

[0013] (8) Calculate the electrode thickness expansion rate under half-charge = {[1+(T2-T1) / (T1-foil thickness)]*[1+(T7-T0) / (T0-foil thickness)]-1}*100%; Calculate the electrode thickness expansion rate under full charge = {[1+(T2-T1) / (T1-foil thickness)]*[1+(T8-T0) / (T0-foil thickness)]-1}*100%.

[0014] A further technical solution is that the compaction in step (2) is set to two gradients, including maximum material compaction and design compaction.

[0015] A further technical solution is that the number of punches in step (1) is 10 pcs, and the electrode area is 0.00201m². 2 The number of holes punched in the empty foil is 5pcs.

[0016] A further technical solution is that the temperature of the oven in step (4) is 85°C and the vacuum baking time is 16-24h.

[0017] A further technical solution is that the physical expansion rate of the electrode in each stage of steps (3)-(5) is equal to (the thickness of the electrode in each stage - the initial thickness T1) / (the initial thickness T1 - the foil thickness) * 100%.

[0018] A further technical solution is that in step (7), the number of battery cells disassembled is 3-5 pcs, and 3-5 thickness data are collected for each pcs battery cell, abnormal points are removed and the average value is taken.

[0019] The present invention has the following advantages:

[0020] This invention can quickly calculate the electrode expansion rate at each stage by recording the electrode thickness of the lithium-ion battery at each stage. By disassembling the pre-charged half-charged and fully charged cells after capacity testing and recording the electrode thickness, the electrode thickness expansion rate of the lithium-ion battery under half-charge and full-charge conditions can be obtained. This invention is simple to operate, has high accuracy, and can effectively evaluate the electrode thickness expansion changes of lithium-ion batteries, which is beneficial for designing the initial thickness dimensions of pouch cells. Attached Figure Description

[0021] Figure 1 This describes the variation in the thickness of the positive electrode sheet under different process stages in this invention.

[0022] Figure 2 This describes the variation in the thickness of the negative electrode sheet under different process stages in this invention. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. The components of the embodiments of the present invention described and shown herein can be arranged and designed in various different configurations.

[0024] Therefore, the following detailed description of embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0025] Example 1:

[0026] Taking the U436483P battery electrode as the research object, the positive electrode is lithium cobalt oxide, the negative electrode is graphite, and the electrolyte is fast-charging type. After the battery electrode is made according to the design process, two large positive and negative electrode sheets are reserved for use. In this embodiment, the thickness of the positive electrode foil is 10μm and the thickness of the negative electrode foil is 6μm.

[0027] 1. Take unrolled double-sided electrode sheets (positive and negative), and punch holes using a punching machine. Punch 3 holes in each electrode sheet, with an electrode area of ​​0.00201 m². 2 Weigh the electrode sheets. Take 5 blank foils with holes punched in them, with the positive electrode being aluminum foil and the negative electrode being copper foil. Weigh them and take the average weight, which is the foil weight. Calculate the areal density: areal density = (electrode sheet weight - foil weight) / 0.00201. In this embodiment, the calculated areal density of the positive electrode is 379 ± 7.4 g / cm³. 3 The negative electrode surface density is 199.4 ± 3.9 g / cm³. 3 ;

[0028] 2. Two compaction gradients are set, including the maximum material compaction, where the positive gradient is 4.2 and the negative gradient is 1.75. The positive gradient in the design compaction is 4.05 and the negative gradient is 1.73. Roll the electrode sheet to the thickness = areal density / compaction + foil thickness, and record it as the initial thickness T1.

[0029] 3. Place the electrode sheet in the workshop and record the electrode sheet thickness T2 one day later. While waiting for the regular electrode sheet to be wound, measure the thickness of the punched electrode sheet T3. After the top and side sealing of the regular electrode sheet is completed, measure the thickness of the punched electrode sheet T4 before baking.

[0030] 4. Place the electrode in an 85℃ oven and vacuum bake for 16-24 hours, and record the electrode thickness T5 after baking;

[0031] 5. Place the baked electrode into a material box containing electrolyte. After 36-48 hours, wipe the electrolyte off the surface of the electrode or wait for the electrolyte to evaporate completely. Record the electrode thickness T6.

[0032] 6. Control the rolling thickness of the experimental electrode to the middle limit of the design thickness, and record the electrode thickness T0;

[0033] 7. Disassemble 3 cells of lithium battery at 50% SOC half charge after precharge and 100% SOC full charge after capacity testing. Record the electrode thickness T7 after precharge half charge and T8 after capacity testing. Collect 3-5 thickness data for each cell, remove outliers, and the average value is the required value.

[0034] 8. Calculate the electrode thickness expansion rate under half-charge = {[1+(T2-T1) / (T1-foil thickness)]*[1+(T7-T0) / (T0-foil thickness)]-1}*100%; Calculate the electrode thickness expansion rate under full charge = {[1+(T2-T1) / (T1-foil thickness)]*[1+(T8-T0) / (T0-foil thickness)]-1}*100%.

[0035] The thickness data recorded during the experiment are shown in Tables 1-4, where the thickness of the positive electrode foil is 10 μm, the thickness of the negative electrode foil is 6 μm, and the areal density of the positive electrode is 379 ± 7.4 g / cm³. 3 The negative electrode surface density is 199.4 ± 3.9 g / cm³. 3 .

[0036] Table 1. Variation of positive electrode sheet thickness under maximum compaction of 4.2.

[0037]

[0038] Table 2. Thickness variation of negative electrode sheet under maximum compaction of 1.75.

[0039]

[0040] Table 3. Thickness variation of the positive electrode sheet under a design compaction of 4.05.

[0041]

[0042] Table 4 shows the thickness variation of the negative electrode sheet under a design compaction of 1.73.

[0043]

[0044]

[0045] The experimental data results show that:

[0046] 1. The compaction of the positive electrode sheet is between 4.05 and 4.2 mm. The thickness expansion rate of the lithium battery electrode sheet is 6.2%-6.5% at 50% SOC and 8%-9% at 100% SOC.

[0047] 2. The negative electrode compaction is between 1.73 and 1.75. The half-electrical expansion rate of the electrode at 50% SOC is 11.3%-11.6%, and the expansion rate at 100% SOC is 17.9%-19.4%.

[0048] Based on the measured expansion rates of the positive and negative electrodes, it is convenient to effectively evaluate and design the initial thickness dimensions of the lithium-ion battery.

[0049] Example 2:

[0050] The battery uses U436483P type electrode sheets, with a positive electrode foil thickness of 10μm and a negative electrode foil thickness of 6μm. The positive electrode areal density is 379g / cm³. 3 The negative electrode surface density is 199 g / cm³. 3 Three positive and three negative electrode pieces were punched according to the specifications of the punching machine. The design compaction thickness of the positive electrode was 4.05 mm, and the design compaction thickness of the negative electrode was 1.73 mm. The plates were compacted and rolled to the required thickness according to the given design. The thickness changes of the positive and negative electrode pieces at different process steps were measured in the same order as in Example 1 to determine the thickness changes of the positive and negative electrode pieces at half-charge and full-charge conditions. Figures 1-2 As shown, the unit of measurement for thickness is um.

[0051] Based on the test results, the half-electrostatic expansion rate of the positive electrode at 50% SOC is calculated as follows: {[1+(T2-T1) / (T1-foil thickness)]*[1+(T7-T0) / (T0-foil thickness)]-1}*100%={[1+(111-109) / (109-10)]*[1+(114-109) / (109-10)]-1}*100%=6.5%.

[0052] The half-electro-expansion rate of the negative electrode is: {[1+(T2-T1) / (T1-foil thickness)]*[1+(T7-T0) / (T0-foil thickness)]-1}*100%={[1+(139-134) / (134-6)]*[1+(144-134) / (134-6)]-1}*100%=11.3%

[0053] The positive electrode expansion rate of the battery at 100% SOC is:

[0054] {[1+(T2-T1) / (T1-foil thickness)]*[1+(T8-T0) / (T0-foil thickness)]-1}*100%={[1+(111-109) / (109-10)]*[1+(116-109) / (109-10)]-1}*100%=8.8%,

[0055] The full-charge expansion rate of the negative electrode is:

[0056] {[1+(T2-T1) / (T1-foil thickness)]*[1+(T8-T0) / (T0-foil thickness)]-1}*100%={[1+(139-134) / (134-6)]*[1+(152-134) / (134-6)]-1}*100%=17.9%.

[0057] Based on the measured expansion rates of the positive and negative electrodes, the initial thickness dimensions of the designed lithium-ion battery can be effectively evaluated.

[0058] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for testing the electrode thickness expansion rate of a lithium-ion battery under half-charge and full-charge conditions, characterized in that, Includes the following steps: (1) Select the model, take the unrolled double-sided electrode sheet, punch it with a punching machine, weigh the electrode sheet weight and area, punch the empty foil, weigh the foil weight and thickness, and calculate the areal density = (electrode sheet weight - foil weight) / electrode sheet area. (2) Based on the areal density and compaction parameters of the electrode sheet, roll the electrode sheet to thickness = areal density / compaction + foil thickness, and record it as the initial thickness T1; (3) Place the electrode in the workshop and record the electrode thickness T2 after one day. When waiting for the conventional electrode to be wound, measure the thickness of the punched electrode T3. After the conventional electrode is sealed on the top and side, measure the thickness of the punched electrode T4 before baking. (4) Place the electrode in an oven for vacuum baking and record the electrode thickness T5 after baking; (5) Place the baked electrode into a material box containing electrolyte. After 36-48 hours, wipe the electrolyte off the surface of the electrode or wait for the electrolyte to evaporate completely. Record the electrode thickness T6. (6) Control the rolling thickness of the experimental electrode to the middle limit of the design thickness and record the electrode thickness T0; (7) Disassemble the lithium battery cells at 50% SOC half-charge after pre-charging and 100% SOC full-charge after capacity testing, and record the electrode thickness T7 after pre-charging and the electrode thickness T8 after capacity testing. (8) Calculate the thickness expansion rate of the half-electrode sheet = {[1+(T2-T1) / (T1-foil material)} [1+(T7-T0) / (T0-foil thickness)]-1}*100%; Calculate the electrode thickness expansion rate under full charge = {[1+(T2-T1) / (T1-foil thickness)]*[1+(T8-T0) / (T0-foil thickness)]-1}*100%.

2. The method for testing the electrode thickness expansion rate of a lithium-ion battery under half-charge and full-charge conditions according to claim 1, characterized in that: In step (2), compaction is set to two gradients, including maximum material compaction and design compaction.

3. The method for testing the electrode thickness expansion rate of a lithium-ion battery under half-charge and full-charge conditions according to claim 1, characterized in that: In step (1), the number of double-sided electrode punches is 6pcs, the electrode area is 0.00201m², and the number of empty foil punches is 5pcs.

4. The method for testing the electrode thickness expansion rate of a lithium-ion battery under half-charge and full-charge conditions according to claim 1, characterized in that: In step (4), the oven temperature is 85°C and the vacuum baking time is 16-24 hours.

5. The method for testing the electrode thickness expansion rate of a lithium-ion battery under half-charge and full-charge conditions according to claim 1, characterized in that: In steps (3)-(5), the physical expansion rate of the electrode at each stage is equal to (electrode thickness at each stage - initial thickness T1) / (initial thickness T1 - foil thickness) * 100%.

6. The method for testing the electrode thickness expansion rate of a lithium-ion battery under half-charge and full-charge conditions according to claim 1, characterized in that: In step (7), the number of battery cells disassembled is 3-5 pcs, and 3-5 thickness data are collected for each pcs of battery cell. Abnormal points are removed and the average value is taken.

Citation Information

Patent Citations

  • Measuring system and method for measuring expansion ratio of negative electrode of softly-packaged lithium battery

    CN109959360A

  • Method for testing expansion rate of silicon-based negative electrode material

    CN115524377A